Efficacy of removing calcium hydroxide deposits from endodontic instruments prior to sterilization using different cleaning methods - Popović Jelena; Nikolić Marija; Mitić Aleksandar; Stošić Nenad; Barac Radomir; Stanković Antonije; Milovanović Aleksandra (Serbian Medical Society - Dental Section, Belgrade, 2023)
Introduction Endodontic instruments during root canal treatment come into contact with dentinal debris, irrigation solutions and medication agents, which reminants should be eliminated before sterilization. The aim of the study was to verify the effectiveness of different cleaning methods for removing calcium hydroxide paste residues from the surfaces of the working parts of hand instruments, as well as to propose an effective protocol for cleaning endodontic instruments before sterilization. Material and methods Forty-two new hand endodontic instruments were used to remove calcium hydroxide paste from the filled canals of extracted teeth. After contamination with medication, they were divided into the four groups and subjected to individual decontamination methods - mechanical, chemical and ultrasonic, as well as a combined protocol. The instruments were then observed under a light microscope. The effectiveness of the methods was evaluated based on the amount of residual matter on the surface of the working parts of the instruments. Results The combined protocol showed a statistically significant difference in the achieved level of cleanliness compared to mechanical (ch2 = 12.00 p < 0.05) and chemical methods (ch2 = 12.00 p < 0.05), but there was no statistically significant difference compared to ultrasonic cleaning in disinfectant solution (ch2 = 2.4 p > 0.05). By applying combined protocol, instruments with completely clean surfaces were found, as well as the lowest values of contamination at the level of the entire group of instruments (8.33%). Conclusion The protocol that consisted of mechanical cleaning with a sponge soaked in chlorhexidine gluconate, chemical soaking in sodium hypochlorite, and ultrasonic cleaning in a disinfectant showed the best efficiency in removing calcium hydroxide residues.